IḤSAN IN BUSINESS: A REFLECTION ON THE B - Amran Rasli, Abu Saim Md. Shahabuddin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
IḤSAN IN BUSINESS: A REFLECTION ON THE B